Ethnoscience-Based Interactive Multimedia to Improve Scientific Literacy in Chemical Equilibrium Materials - Nur Lailil Aprilia; Achmad Lutfi (Hydrogen: Jurnal Kependidikan Kimia, 2023)
This study aims to obtain interactive multimedia that can improve scientific literacy skills in chemical equilibrium material. The method used in this research is the Borg and Gall Research and Development (R&D) model with three stages, namely the preliminary study stage, the media development stage and theoretical validity, and the media trial stage. The trial design used was one group pretest posttest. The data obtained was in the form of a validity score determined by the mode, the practicality score from the results of the student response questionnaire was analyzed by percentage, and the effectiveness data in the form of pretest-posttest results were analyzed using n-gain. Based on the results of the study, the validity mode was obtained, namely a score ≥ 3 in each aspect, a practicality score of 94,4%, an n-gain score of 0,8088 in the high category, and classical completeness of 91,43%, so that ethnoscience-based interactive multimedia can be declared feasible. to improve scientific literacy skills on chemical equilibrium material.